-6(2x-9)=-12-54

Simple and best practice solution for -6(2x-9)=-12-54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2x-9)=-12-54 equation:



-6(2x-9)=-12-54
We move all terms to the left:
-6(2x-9)-(-12-54)=0
We add all the numbers together, and all the variables
-6(2x-9)-(-66)=0
We add all the numbers together, and all the variables
-6(2x-9)+66=0
We multiply parentheses
-12x+54+66=0
We add all the numbers together, and all the variables
-12x+120=0
We move all terms containing x to the left, all other terms to the right
-12x=-120
x=-120/-12
x=+10

See similar equations:

| 74-1x=984x | | 6x+9x=4x+25 | | 12y+-6=10 | | F(4)=12x+7 | | A=6x-35° | | 204-v=104 | | 10=(x-(0.15x+125))/x | | 62-v=280 | | 293=-x+156 | | 9w=6w+9 | | 10x=x-(0.15x+125) | | 9w=6w | | -7x=+2=-4x-7 | | 293=-x=156 | | 64=-y+192 | | 15x/1x=1 | | 66=3/4x | | -2=m-8 | | 2m+25=8m-5 | | 24=12+b | | 4m^2+16m+33=0 | | 15=n/19 | | b/13-36/13=12/13 | | 4+3v=5v-7+7 | | 6m+13=8m-3 | | 5x-7-8x=13+4x-3x | | 5y-(-13)=12 | | 28=3x^2-5x | | X-9=1-x | | 5b-+12=43 | | 7-6m=-8m+1 | | 2x-4=5x-27 |

Equations solver categories